Analysis of Psychological Test Manuals Approved by Satepsi for Adult Assessment - Reppold, Caroline Tozzi (2018)
In this article, the psychological test manuals considered favorable by Satepsi to assessment of personality, emotional/social attributes or professional/work-related aspects in adults were analyzed in relation to the indication of use, authorship, publisher, normative studies and constructs. Of the 173 tests listed in the Satepsi in July 2017, 65 were included: 33 are intended for personality assessment (19 scales/inventories and 14 projective tests), 20 to assessment of emotional/social attributes and 12 related to professional orientation or work context. Most of the tests present in their manuals the information investigated. Although there are in some cases discrepancies between the indication of use of the test and the age of Brazilian standardization samples, the data lead to the conclusion that the quality of the information consulted in the manuals represents an advance in relation to the panorama described by researchers of the area in the 1990s and 2000s.